CLINICAL PRESENTATION OF HIV-INFECTED PATIENTS IN A PSYCHIATRIC HOSPITAL IN SOUTH AFRICA - Chetty, Shren; Naidu, Kalai (African Journal of Infectious Diseases (AJID), 2018)
Background: Africa is profoundly stricken by the HIV pandemic. People living with HIV/AIDS are more likelyto be diagnosed with psychiatric disorders than the general population. We describe the prevalence of differentmood and psychiatric disorders in HIV/AIDS infected patients with serious mental illness.Materials and Methods: We retrospectively sourced data from 105 patient files, at Weskoppies Hospital,between January 2012 and December 2016.Results: 56 patients had a psychotic disorder; 27 patients had a mood disorder and three patients had a cognitivedisorder. Multiple diagnoses were observed in seven patients with a mood and psychotic disorder; ten patientswith a psychotic and cognitive disorder and one patient with a mood and cognitive disorder. One patient had allthree diagnoses. The most common medical co-morbidities were hypertension (15.24%) and tuberculosis(13.33%).Conclusion: Mentally ill patients who are HIV positive mostly present with mood and psychotic disorders.Clinicians need to be vigilant to detect neuropsychiatric manifestations of HIV infection to effectively manageand optimise treatment. This study highlights the need for further intervention in these vulnerable patients.